THE STRUGGLE FOR SURVIVAL: THIRD GENDER IN MAHESH DATTANI’S SEVEN STEPS AROUND THE FIRE - M. Saravanan; V.S. Shiny (ShodhKosh: Journal of Visual and Performing Arts, 2024)
Indian playwrights like Mahesh Dattani emerged when the British sought to impose their culture and language. They blend English with native sensibilities to critique colonial dominance and address modern societal issues. Dattani’s plays, particularly Seven Steps Around the Fire, explore themes of gender and class oppression, focusing on the marginalized hijra (transgender) community. Dattani portrays their societal exclusion and the violence they endure and exposes the hypocrisy of a culture that simultaneously seeks their blessings yet denies them fundamental rights. Through the character of Uma Rao, Dattani delves into the complex interplay between power, class, and gender. Uma, the voice of humanity and reason in the play, empathizes with the hijras and challenges oppressive societal norms. However, the powerful minister, representing the elite, uses his influence to hide the truth about a hijra's murder. It reflects the broader systemic oppression faced by marginalized communities. Dattani’s work thus not only critiques the societal oppression of transgenders but advocates for compassion and understanding as pathways to meaningful change.